Assessment of Reservoir Qualities of The Yolde Formation Along Pantami Stream Channel, Gongola Sub- Basin, Northern Benue Trough, Ne Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2025)
The Yolde Formation conformably overlies the Bima Sandstone. It is Cenomanian inage and marks the onset of marine transgression into the Gongola sub basin of theBenue Trough. Comprises mainly of sandstones, limestone, shales, clays andclaystones. The study section exposed about 70m thick of the Yolde Formation alongPantami stream channel, Gombe, Gombe town. Several lithofacies of sandstonesand mudstones ware identified. The sandstones vary from very fine, fine, mediumto coarse grained. Sedimentary structures identified include parallel, planar cross-beddings, trough cross-beddings and herringbone cross-stratification. Lithofaciesanalysis shows series of fining and coarsening upward sequences which indicateincrease and decrease in depositional energies within the environment.Petrographic analysis shows that the sandstone samples are texturally matured.The Quartz grains are both monocrystalline and polycrystalline in nature while thesub-rounded to rounded nature of the grains suggests that the sediments weretransported from a long distance. The framework components of the sandstonesbased on the QFR plot shows that the sandstones are Quartzarenite, Sublithareniteto Litharenite and Subarkorse to Arkosic in nature. Grainulometric analysis showsthat the sandstones are moderately to poorly sorted (1.0-2.0)∂I, the grains sizes arefine to medium (2.7-0.9)MZ platykurtic to very leptokurtic (0.9-1.9)KG and arecoarse to strongly fine skewed (0.04-0.6)SKI. From the histograms, the sedimentsare generally unimodal indicating the same sources of sediments, typical of fluvialenvironment. Also, the poor sorting and fine skewness is as a result of increase anddecrease in depositional energies by river/wave processes which was furtherbuttressed by bivariate plots. Porosity of the samples assessed indicate moderateto good porosity and the permeability assessment indicate moderate to goodpermeability as well.